Additive effects of social and non‐social attention during infancy relate to later autism spectrum disorder. Issue 4 (23rd February 2014) - Bedford, Rachael; Pickles, Andrew; Gliga, Teodora; Elsabbagh, Mayada; Charman, Tony; Johnson, Mark H.
Abstract: Emerging findings from studies with infants at familial high risk for autism spectrum disorder (ASD), owing to an older sibling with a diagnosis, suggest that those who go on to develop ASD show early impairments in the processing of stimuli with both social and non‐social content. Although ASD is defined by social‐communication impairments and restricted and repetitive behaviours, the majority of cognitive theories of ASD posit a single underlying factor, which over development has secondary effects across domains. This is the first high‐risk study to statistically differentiate theoretical models of the development of ASD in high‐risk siblings using multiple risk factors. We examined the prediction of ASD outcome by attention to social and non‐social stimuli: gaze following and attentional disengagement assessed at 13 months in low‐risk controls and high‐risk ASD infants (who were subsequently diagnosed with ASD at 3 years). When included in the same regression model, these 13‐month measures independently predicted ASD outcome at 3 years of age. The data were best described by an additive model, suggesting that non‐social attention, disengagement, and social attention as evidenced by gaze following, have a cumulative impact on ASD risk. These data argue against cognitive theories of ASD which propose that a single underlying factor has cascading effects across early development leading to an ASD outcome, and support multiple impairment models of ASD that are more consistent with recent genetic and neurobiological evidence. Abstract : Emerging findings from studies with infants at familial high risk for autism spectrum disorder (ASD), owing to an older sibling with a diagnosis, suggest that those who go on to develop ASD show early impairments in the processing of stimuli with both social and non‐social content. Although ASD is defined by social‐communication impairments and restricted and repetitive behaviours, the majority of cognitive theories of ASD posit a single underlying factor, which over development has secondary effects across domains. This is the first high‐risk study to statistically differentiate theoretical models of the development of ASD in high‐risk siblings using multiple risk factors.